Interpretation of Balinese Goddess Saraswati Worship Ritual Into Illustrative Musical Composition in Multimedia Music - Pratama, Yuda; Hendri, Yon; HR, Hafif (Scoring: Journal of Film Music, 2023)
ABSTRAKArtikel ini memuat tentang karya musik ilustrasi yang berangkat dari prosesi  Ritual Pemujaan Dewi Saraswati  yang dilaksaanakan  di Bali pada setiap tahunnya yang dilakukan pada pagi hari. Pengkarya menghadirkan suasana sesuai alur cerita dari tahap persiapan hingga tahan prosesi ritual,. Tujuan dari penulisan artikel ini adalah untuk mewujudkan komposisi musik ilustrasi dalam bentuk garapan multimedia dengan mengambil ide musical  dari mantra pemujaan terhadap Dewi Saraswati.  Metode pencitaan yang digunakan  dalam penggarapan karya ini adalah  metode penciptaan A.M. Hawkins yang terdiri atas tiga tahap yaitu ; (2) Tahap explorasi , (2) tahap eksperimen, (3) perwujudan.  Penggarapan komposisi musik  ilustrasi  ini menghasilkan komposisi musik multimedia yang berjudul “ Ilustrasi of Music “Ritual Pemujaan Saraswati dalam bentuk free formKata Kunci:Ritual Pemujaan Dewi Saraswati; Musik Ilustrasi; Musik MultimediaABSTRACTThis article contains an illustrated piece of music that departs from the procession of the Ritual Worship of Dewi Saraswati which is held in Bali every year which is done in the morning. The creators present the atmosphere according to the storyline from the preparation stage to the ritual procession. The purpose of writing this article is to create an illustrated musical composition in the form of a multimedia work by taking the musical idea from the mantra of worship of Dewi Saraswati. The creation method used in the creation of this work is A.M. Hawkins which consists of three stages namely; (2) Exploration stage, (2) experimental stage, (3) embodiment. The cultivation of this illustration music composition resulted in a multimedia music composition entitled "Illustration of Music" Saraswati Worship Ritual in free form Keywords: Goddess Saraswati Worship Rituals; Illustrated Music; Multimedia Music.